FEVER IN UNDER-FIVES: EXAMINING PARENTAL KNOWLEDGE, PERCEPTIONS, AND THE IMPACT OF SOCIO-DEMOGRAPHIC DETERMINANTS - Dr. TEERUPATI PRASUNA YADAV; Dr. Shaik Abdul Deepthi Shalma; Dr. Rajendhra naidu. V (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
The research examines how parents understand and handle child fevers under five-year-olds while analyzing their behavior through social and demographic characteristics. The survey results showed that 60% of parents had inadequate fever management knowledge while parents aged 26-35 displayed superior comprehension of fever care. The research findings show major shortcomings in fever care practices because 78.75% of parents chose antipyretics (paracetamol) and 51% used sponging. The survey results showed that 30.75% of parents misused antibiotics to treat fever because they did not comprehend the nature of fevers. Parental age together with education level and socioeconomic status and geographical location play major roles in determining how parents manage fever symptoms. Parents with less formal education who lived in lower income areas and resided in rural locations demonstrated limited understanding of proper fever treatment. The most scared complication for parents was febrile seizures which caused mothers and other parents to develop fever phobia leading to unnecessary medical visits. The research establishes the necessity of specific educational programs that must focus on rural and underprivileged regions to teach parents about fever knowledge and management while minimizing incorrect fever treatment and anxiety. Educational interventions for these knowledge gaps will improve child fever management while decreasing healthcare expenses and resulting in improved health outcomes.